The Greek debt crisis: Likely causes, mechanics and outcomes - Michael G. Arghyrou; John D. Tsoukalas (Cardiff University, Cardiff Business School, 2010)
We use insights from the literature on currency crises to offer an analytical treatment of the crisis in the market for Greek government bonds. We argue that the crisis itself and its escalating nature are very likely to be the result of: (a) steady deterioration of Greek macroeconomic fundamentals over 2001-2009 to levels inconsistent with longterm EMU participation; and (b) a double shift in markets' expectations, from a regime of credible commitment to future EMU participation under an implicit EMU/German guarantee of Greek fiscal liabilities, to a regime of non-credible EMU commitment without fiscal guarantees, respectively occurring in November 2009 and February/March 2010. We argue that the risk of contagion to other periphery EMU countries is significant; and that without extensive structural reforms the sustainability of the EMU is in question.
Keywords: F31; F33; F34; F41; F42; F50; 330; currency crises; bonds market; expectations; fiscal guarantees; contagion; Öffentliche Schulden; Insolvenz; Kreditabkommen; Wirtschaftskrise; Griechenland; Europäische Wirtschafts- und Währungsunion